Analysis of Opportunities and Challenges in Implementing A Gender-Based Circular Economy of Gonggong Shell Waste in Padang Melang Beach Tourism - Rosnah, Rosnah; Ismail, Khodijah; Zulfikar, Andi (Agrikan Jurnal Agribisnis Perikanan, 2024)
The research was conducted in the tourist area of Padang Melang Beach, Batu Berapit Village, Anambas. This research used descriptive qualitative research methods, with data sources from FGDs, interviews and questionnaires. The population of this study is coastal communities, the sample was taken by purposive sampling. The opportunity for a circular economy to occur in the Padang Melang Beach tourism area, Batu Berapit Village, Anambas, is that it already has tourist activities. It can be seen from the components that are the center of increasing tourism activities in the area, namely tourists, settlements and pokdarwis institutions with a tourist linkage value of 26.20, pokdarwis groups of 18.50 and settlements of 27.70. While the challenge is that the participation of village government and BUMDES institutions as a marketing sector has not been running, due to the inactivity of BUMDES as a village-owned business entity that has a major contribution to economic activities in the village.